An inverted ring oscillator noise-shaping time-to-digital converter with in-band noise reduction and coherent noise cancellation - Yi, Xiang (2020)
This article presents a noise-shaping time-to-digital converter (TDC) based on an inverted ring oscillator (IRO). By inverting the oscillation direction, the proposed IRO-TDC achieves quantization error and mismatch noise shaping, in-band noise reduction, coherent noise cancellation, and low disturbance to power supply at the same time. A noise model is proposed to analyze the noise performance of the proposed TDC, and to compare its noise with TDCs based on gated ring oscillator (GRO) and switched ring oscillator (SRO). An IRO-TDC prototype is fabricated in a 65 nm CMOS technology to verify the proposed IRO technique and noise model. With a sampling rate of 200 MS/s, the TDC achieves an integrated noise of 196 fsrms in a 3 MHz bandwidth with a constant power dissipation of 13.2 mW. The measured coherent noise cancellation ratio is up to 36.4 dB. To the best of our knowledge, this is the first demonstration of an oscillator utilizing oscillation inversion for noise reduction and coherent cancellation to protect the TDC from power supply noise, ground noise, and substrate noise. Due to its noise cancellation and low disturbance to power supply, the proposed IRO technique also alleviates the design complexity of power supply in future TDC applications.